Human Side Of Total Quality Management In Yemen Industrial Companies - Naseer Ahmed Nasser Habtoor
An empirical investigation into the extent of total quality management practices was conducted in the Yemeni industrial sector. It evaluates the relationship between human factors of quality management, quality improvement practices, and organization performance. More specifically, this study examines direct and indirect impact of human factors of quality management on quality improvement practices and organization performance. A quantitative approach by designing questionnaire was used to collect the data from 87 industrial companies. Three quality managers from each company were participated in this study, and a total of 210 managers responded to the survey. The response rate was 80%. SPSS program was used to test factor analysis, reliability analysis, descriptive statistic, and correlation analysis. Structural equation modeling (SEM) technique was carried out by Amos program to evaluate the hypotheses in the research model. This study contributes to the literature of total quality management as one of a fewer studies interest on human side of quality management and as the first to report in Yemen and Middle East countries as well. The findings support the relationship between the variables found that human factors of quality management directly impact quality improvement practices and organization performance. Findings also reveal direct positive impact of quality improvement practices on organization performance. Moreover, the findings provide evidence reveals a significant indirect impact of human factors of quality management on organization performance via their direct impact on quality improvement practices. In conclusion, this study provides evidence for the significant positive impact of human factors for the implementation of quality improvement and organization performance. Therefore, the findings of this study should be useful for researchers and managers, especially in Yemeni industrial companies. For further work, this study can be expanded to other Middle East countries, and also it may include more human factors.